Da’wah Communication Strategy as an Effort to Reform Muhammadiyah Cadreization to Carry the Tajdid Mission in IMM North Lampung - Marini Marini; Farabi Ferdiansyah; Lida Nelis Sumia; Nabila Widi Alfany; Hani Melisa; Muhamad Afdoli Ramadoni (Fakultas Dakwah dan Komunikasi Universitas Islam Negeri Raden Fatah Palembang, 2026)
Muhammadiyah’s cadreization has historically functioned as a strategic mechanism for producing religious, intellectual, and socially committed Muslim cadres who are able to carry the mission of tajdid. However, in the context of contemporary student organizations, cadreization faces new challenges, particularly the shifting patterns of youth communication, the rise of digital media, and the need to reinterpret da’wah approaches in ways that remain relevant to students’ social realities. Previous studies on Muhammadiyah cadreization have largely emphasized ideological formation, organizational regeneration, or normative understandings of tajdid. Meanwhile, limited attention has been given to how da’wah communication strategies are developed and practiced by the Ikatan Mahasiswa Muhammadiyah (IMM) at the local level as an effort to reform cadreization. This gap is particularly important in IMM North Lampung, where da’wah activities are carried out through interpersonal communication, organizational forums, and new media platforms. This study focuses on the da’wah communication strategy of IMM North Lampung in strengthening Muhammadiyah cadreization and carrying the mission of tajdid. The concept of tajdid is understood in two dimensions: purification in matters of creed and worship, and renewal in responding to social, intellectual, and humanitarian challenges. The study examines how IMM North Lampung formulates da’wah messages, selects communication channels, builds cadre engagement, and integrates religious, intellectual, and humanistic values into its cadreization process. By highlighting da’wah communication as a strategic instrument of cadre reform, this study contributes to a deeper understanding of how Muhammadiyah’s student cadres negotiate Islamic renewal within contemporary youth and digital communication contexts.